(untitled) (Nepal Medical College Journal, 2023)
Myocardial infarction the most common form of coronary heart disease is a growing health issue in developing countries. The number and magnitude of the disease is expected to grow without awareness and preventive interventions. Therefore, this study was carried out to find out knowledge and practice regarding myocardial infarction prevention among the visitors of cardiac center. A descriptive cross sectional study was conducted among 278 patient’s visitors attending Manmohan Cardio-Thoracic Vascular and Transplant Centre from June 2021-August 2021. The selection of the study area and data collection was done using Convenient sampling technique. SPSS version 16 was used for data entry and analysis. Descriptive statistics such as median, frequency and inferential statistics such as chi-square tests were used. The study revealed over 2/5th (42.8%) of respondents were between age group of 41-50 years. Majority (92.1%) were literate among which over a third (37.5%) had secondary level of education. The practice of blood pressure measurement, blood sugar and blood cholesterol measurement was reported by 76.1%, 59.1% and 31.4% respectively. Level of knowledge was adequate in 24.2% of respondents. Significant association was found between level of knowledge and sex (P=0.015), religion (P=0.009), occupation (P=0.017), and literacy status (P=0.001). Level of knowledge was found to be adequate in low percentage of the respondents. As myocardial infarction is a trending non-communicable disease, nationally there is the necessity of conducting extensive health awareness program, campaigns regarding its prevention.